SUCH A NEURON HAS A ROLE IN THE DEVELOPMENT OF CEREBRAL PALSY (Modern education and development, 2025)
The article explains in detail the importance of recurrent neural networks in various areas of society, their principles and types, how they are used in natural language processing, speech recognition, financial forecasting, the automotive industry, healthcare, video analysis, and many other areas. The prospects for improving existing technologies and creating new opportunities using RNNs are considered.